Public Health and the COVID-19 pandemic: challenges for global health (Research, Society and Development, 2020)
Public Health aims to achieve as much understanding as possible of the phenomenon of human life related to the health-disease process and to obtain the highest attainable standards of health and well-being of the population. This field of knowledge contributes to the fight against the COVID-19 pandemic, with epidemiology as the highlight. Objective: to promote a reflection on health and the current pandemic with the proposal of the present and future construction of a more integrative and cooperative global health, with health services accessible to the populations. Method: literature review based on research carried out on books and database of scientific publications (VHL and Scielo). Results: scientific texts considered relevant for the discussion were included in this review, with the themes of Public Health and COVID-19. Discussion: the discussion was organized into four categories, namely: COVID-19 epidemiological challenges for health; measures to contain the pandemic; the impact of the pandemic on mental health; the social and economic impact of the pandemic. Conclusion: there are still many challenges for collaborative global health among different countries in the world.